2016
DOI: 10.1021/acs.chemmater.6b02845
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermoelectric Properties of Noble Metal Ternary Chalcogenide Systems of Ag–Au–Se in the Forms of Alloyed Nanoparticles and Colloidal Nanoheterostructures

Abstract: ABSTRACT:The optimization of a material functionality requires both the rational design and precise engineering of its structural and chemical parameters. In this work, we show how colloidal chemistry is an excellent synthetic choice for the synthesis of novel ternary nanostructured chalcogenides, containing exclusively noble metals, with tailored morphology and composition and with potential application in the energy conversion field. Specifically, the Ag-Au-Se system has been explored from a synthetic point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 80 publications
1
25
0
Order By: Relevance
“…Mixed silver-gold sulfides and selenides, including nanoparticulate ones, have attracted intense interest as minerals and natural sources of precious metals [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and due to high ionic conductivity, tunable optical characteristics, thermoelectric and other properties promising for materials applications [15][16][17][18][19]. Gold chalcogenides, in particular gold selenide, are much less examined, despite aqueous Au chalcogenide-derived complexes play the crucial role as carriers of gold in hydrothermal fluids and brines (e.g., [20][21][22][23][24][25] and references therein), and AuSe, Au(Se,S) and Au(Te,Se,S) phases in intergrowths with native gold have been found in the high-sulfidation epithermal deposits formed from acidic fluids [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed silver-gold sulfides and selenides, including nanoparticulate ones, have attracted intense interest as minerals and natural sources of precious metals [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and due to high ionic conductivity, tunable optical characteristics, thermoelectric and other properties promising for materials applications [15][16][17][18][19]. Gold chalcogenides, in particular gold selenide, are much less examined, despite aqueous Au chalcogenide-derived complexes play the crucial role as carriers of gold in hydrothermal fluids and brines (e.g., [20][21][22][23][24][25] and references therein), and AuSe, Au(Se,S) and Au(Te,Se,S) phases in intergrowths with native gold have been found in the high-sulfidation epithermal deposits formed from acidic fluids [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is known from chemistry textbooks (for example [38]) that direct interaction between aqueous gold complexes and selenide ions results in precipitation of unstable gold selenides with unclear compositions. Preparation of nanoscale materials containing gold selenide have been described in a few publications [17,[39][40][41][42][43][44][45]. Nath and co-workers [39] have synthesized "AuSe nanoalloys" via fusion of elemental Au and Se nanoparticles in a micellar solution, typically with an excess of Au NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Elemental analysis (Figure S3, Supporting Information) also supports their alloyed‐type composition of these nanostructures. Partial sulfurization of Ag(0) particles turning to Ag‐Ag 2 S alloyed material heterostructures is widely known . Figure c,d shows the TEM and HRTEM images of these Au‐treated bimetallic and binary alloyed semiconductor heterostructures.…”
Section: Resultsmentioning
confidence: 99%
“…In the Se analogue we observed that the Se(-II) was working as a sacrificial anion to reduce Au(III) to Au(I), and indeed an amorphous Se layer was observed surrounding ternary NPs. 22 In fact, HRTEM micrographs also point to the formation of a thin amorphous shell after the cation exchange reaction (Figures 3 and 5). Although in principle, S(-II) should be less reducing than Se(-II), experimentally the nucleation of Au(0) is observed in all samples prepared with S and could not be avoided, contrary to what happens with Se.…”
Section: Reaction Mechanismmentioning
confidence: 91%